Corporate Governance and R&D Strategic Decision Making - Lee-Anne C Johennesse; I Gusti Agung Musa Budidarma Budidarma (East Asian Journal of Multidisciplinary Research, 2022)
This study seeks to develop understanding from the literature the important relationship between corporate governance mechanism especially board characteristics and R&D strategic decision making. Some board characteristics, such as board size and independence are positively associated with firm performance. Directors of different ethnic, cultural backgrounds and different nationalities stimulate a firm to improve or develop new products. Older directors are less risk-tolerant than younger ones and invest less in risky R&D investments. The effect of board size on performance is negative and significant, while it has a positive and significant impact on R&D investment. Therefore, board characteristics are the considerable factors in affecting the effective R&D strategic decision making.